Anticancer maintenance chemotherapy prolonged prognosis of metastatic urothelial carcinoma patients: A single institute retrospective study using propensity score matching. (24th August 2022) - Yamamoto, Akinaru; Kawashima, Atsunari; Uemura, Toshihiro; Yamamichi, Gaku; Tomiyama, Eisuke; Koh, Yoko; Matsushita, Makoto; Kato, Taigo; Hatano, Koji; Uemura, Motohide; Imamura, Ryoichi; Nonomura, Norio
Abstract : Objectives: To evaluate the therapeutic efficacy of anticancer maintenance chemotherapy for metastatic urothelial carcinoma. Methods: We retrospectively compared the clinical outcomes of 74 patients with metastatic urothelial carcinoma who had been treated with or without anticancer maintenance chemotherapy between 2006 and 2020 at Osaka University Hospital. Progression‐free survival and cancer‐specific survival periods were calculated using the Kaplan–Meier method starting from the end date of induction chemotherapy. The backgrounds of patients who had treated with or without anticancer maintenance chemotherapy were adjusted using the propensity score matching method. Results: Twenty‐nine patients had undergone anticancer maintenance chemotherapy, whereas 45 patients had not. The median progression‐free survival periods were 18.7 and 5.6 months ( p = 0.0209), and the median cancer‐specific survival periods were 25.1 and 15.2 months ( p = 0.1299), in patients with or without anticancer maintenance chemotherapy respectively. In multivariate analysis, anticancer maintenance chemotherapy significantly prolonged both progression‐free survival (hazard ratio 3.65, 95% confidence interval 1.96–6.78, p < 0.0001) and cancer‐specific survival (hazard ratio 3.05, 95% confidence interval 1.62–5.76, p = 0.0006) in patients with partial response or stable disease after induction chemotherapy. Also, anticancer maintenance chemotherapy significantly prolonged both progression‐free survival (13.1 months vs. 4.9 months, p = 0.0027) and cancer‐specific survival (35.1 months vs. 11.8 months, p = 0.0044) in propensity score matched patients. Conclusions: Anticancer maintenance chemotherapy may be considered the treatment for metastatic urothelial carcinoma patients after induction chemotherapy.